ANALISIS PENGARUH BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PETUGAS AVSEC DI BANDAR UDARA - Fauziah, Syifa; Azzara, Kinaya Indah (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
During the COVID-19 Pandemic, there has been a change in the efficiency and workload of Avsec, and after the Pandemic the number of passengers continued to increase and finally the pattern and workload of Avsec changed again. To understand the changes in Avsec performance, this research aims to determine the influence of workload and work discipline on the performance of Avsec. The research method uses a quantitative approach with primary questionnaire data and a sample size of 56 Avsec at Sultan Babullah Airport in Ternate. The data analysis techniques used are multiple linear regression and descriptive analysis. The research results show that workload and work discipline have different influences on Avsec’s performance in each assignment area. However, the results of the descriptive analysis in each area on average have very high criteria, which means that the workload and work discipline to achieve performance according to security targets/standards is optimal among Avsec at Sultan Babullah Airport in Ternate.